Financial Accessibility and Financial Performance of Small and Medium Enterprises a Case Study of Mukono Municipality - Stella Auma (Uganda Christian University, 2025)
This study examined the relationship between financial accessibility and the financial performance of Small and Medium Enterprises (SMEs) in Mukono Municipality, Uganda. The study was guided by three dimensions of financial accessibility: availability, affordability, and eligibility. A descriptive research design was adopted, and data was collected using structured questionnaires from a sample of SME owners and managers operating within the municipality. Quantitative data was analyzed using descriptive statistics (mean and standard deviation) and Pearson correlation to determine the strength of the relationship between the variables. The findings revealed that the availability of financial services, such as proximity to financial institutions and mobile money platforms, positively influenced SME performance. Affordability of financial services, including interest rates and transaction fees, was found to be a moderate constraint, while eligibility requirements, such as collateral and credit history, also limited access to financial resources for many SMEs. Overall, the study found a significant positive correlation between financial accessibility and financial performance of SMEs, indicating that enhanced access to financial services contributes to improved business outcomes such as increased profits, debt management, and business expansion. The study concludes that addressing financial accessibility challenges can greatly improve the financial health and sustainability of SMEs in Mukono Municipality. It recommends financial institutions and policymakers adopt more SME-friendly approaches, including flexible eligibility criteria, affordable credit products, and broader financial literacy programs
THESIS